2006
DOI: 10.1051/vetres:2006020
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of the lymph node immune response followingMycoplasma mycoidessubsp.MycoidesSC infection in cattle

Abstract: -Contagious bovine pleuropneumonia (CBPP), caused by Mycoplasma mycoides subsp. mycoides biotype Small Colony (MmmSC

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 29 publications
2
22
0
Order By: Relevance
“…In contrast, after 6 days in vitro, CD4 + T cells largely outnumbered all other subsets among CFSElow cells, which resulted in a substantial enrichment of cultures for CD4. These results provide an explanation to previous studies reporting a lack of enrichment for CD4 despite strong activation (i.e., upregulation of CD25) in 5-day-old stimulated cultures [8] and underline the benefits of using CFSE loading in analysis of recall responses. Because of concomitant B-cell proliferation, changes in frequencies of CD4 + T cells was not detected before day 6 while proliferation of these cells was measured as early as day 4 using the CFSE method.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…In contrast, after 6 days in vitro, CD4 + T cells largely outnumbered all other subsets among CFSElow cells, which resulted in a substantial enrichment of cultures for CD4. These results provide an explanation to previous studies reporting a lack of enrichment for CD4 despite strong activation (i.e., upregulation of CD25) in 5-day-old stimulated cultures [8] and underline the benefits of using CFSE loading in analysis of recall responses. Because of concomitant B-cell proliferation, changes in frequencies of CD4 + T cells was not detected before day 6 while proliferation of these cells was measured as early as day 4 using the CFSE method.…”
Section: Discussionsupporting
confidence: 81%
“…In summary, the results presented here extend previous results [7,8] and further support the idea that Th1 memory lymphocytes are involved in the control of CBPP. Vigorous proliferative and T1 biased cytokine recall responses, with a predominant contribution of CD4 + T cells, were observed in cattle that have recovered from CBPP, but not in animals developing the acute form of the disease.…”
Section: Secretion Of Ifn-γ Upon Stimulation Withsupporting
confidence: 90%
See 1 more Smart Citation
“…In CBPP, while short term immunity is elicited by vaccination and long term immunity after recovery, very little is known regarding the mechanisms by which this protection is mediated [16,22]. In a recent study we demonstrated the involvement of cellular immunity in the MmmSC-specific protective immune response [5,6]. However, since CBPP is a respiratory disease, the local humoral response should also play a key role in protection by inhibiting MmmSC growth and potential attachment to host cells.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work indicated that CD4 ϩ T cells make a major contribution to the vigorous T1-biased anamnestic cellular immune response observed for cattle that have recovered from infection (2,3,18). More recently, we demonstrated that MmmSC-specific memory CD4 ϩ T cells comprise two phenotypically and functionally different subsets (19).…”
mentioning
confidence: 62%